"If She Refuses to Have Sex With You, Just Make Her Tipsy": A Qualitative Study Exploring Alcohol-Facilitated Sexual Violence Against Nigerian Female Students. Issue 17 (September 2020) - Dumbili, Emeka W.; Williams, Clare
Most research on alcohol consumption and related sexual violence focuses on Western societies. Drawing on traditional masculinity scripts, this article contributes to the culturally specific understanding of how Nigerian sociocultural constructions of alcohol consumption facilitate sexual violence against women. In-depth interviews were conducted with 31 male and female undergraduate students (aged 19-23 years), exploring how the gendering of alcoholic beverages facilitates men's perpetration of sexual violence against women in a Nigerian university. Thematic analysis was conducted using NVivo 10 software. Men were found to exclude women from consuming beer, which they described as "inappropriate" feminine behavior, confining them to drinking sweetened/flavored alcoholic beverages. To maintain a notion of "respectable" femininity, women consumed these drinks, but this created gender-specific risks. In comparison with beer, sweetened alcoholic beverages have a higher alcohol content, which many of the men were aware of, unlike the women interviewed. Some men admitted buying such drinks for women, pressuring them to drink above their limits and raping them when they were inebriated. Public health interventions that focus on the deep-seated gendered consumption rituals anchored in patriarchal beliefs, the commodification of women's bodies, and the stigmatization of rape victims should be pursued more vigorously in Nigeria and other non-Western societies.